PENGARUH KARAKTERISTIK DEMOGRAFI DAN EKONOMI TERHADAP PERMINTAAN TELUR AYAM BERLABEL DI KAWASAN YOGYAKARTA - Sri Sari Utami; Jangkung Handoyo Mulyo; Lestari rahayu Waluyati (Agro Ekonomi, 2014)
The objective of this research were to analyze the relationships between demographic characteristic ( age and family members) and other factors on demand for labeled eggs. The respondents are consumers who consumed labeled eggs and consisted of 50 labelled eggs consumer who are selected by incidental sampling. The effect of demographic characteristics and other factors were analyzed by using multiple linear regression model. The result indicates that consumption of labeled eggs influenced positively by consumer motivation, consume income and number of family members and influenced negatively by price of labeled eggs.